2009
DOI: 10.1111/j.1600-0633.2008.00346.x
|View full text |Cite
|
Sign up to set email alerts
|

Using motion‐sensitive radio tags to record the activity and behavioural patterns of spawning Atlantic salmon

Abstract: –  In this paper, we describe a method employing motion‐sensing radio transmitters for recording and identifying behavioural patterns and activity of Atlantic salmon spawning under natural conditions. Simultaneous video monitoring verified recorded activity patterns originating from behaviours such as fighting, nest digging and quivering. The method described here enables more accurate determination of the timing and location of spawning compared to conventional location tracking. Motion‐sensing transmitters c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
(43 reference statements)
0
10
0
Order By: Relevance
“…Moreover, studies in other salmonids show that movements in male sockeye salmon ( Oncorhynchus nerka ) decrease as the spawning season progresses ( 34 ) and that most dispersers first homed to their natal streams before dispersing to new spawning grounds ( 31 ). Studies of Atlantic salmon caught in the Teno River show that movement of individuals to other areas is rare close to spawning ( 35 ), and radiotelemetry of individuals has also shown very limited movement during the breeding season ( 36 ). Thus, long-distance movement of individuals visiting this spawning site close to spawning time is highly unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies in other salmonids show that movements in male sockeye salmon ( Oncorhynchus nerka ) decrease as the spawning season progresses ( 34 ) and that most dispersers first homed to their natal streams before dispersing to new spawning grounds ( 31 ). Studies of Atlantic salmon caught in the Teno River show that movement of individuals to other areas is rare close to spawning ( 35 ), and radiotelemetry of individuals has also shown very limited movement during the breeding season ( 36 ). Thus, long-distance movement of individuals visiting this spawning site close to spawning time is highly unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…One mechanism may be that reproductive isolation is due to assortative mating and/or temporal variation in spawning time, rather than spatial isolation. This scenario was assumed to be unlikely, as both 1SW and 3SW spawn at the same time (Karppinen & Erkinaro ; E.N, J.E. & P.O, personal observations with underwater camera monitoring).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies in other salmonids show that movements in male sockeye salmon (Oncorhynchus nerka) decreases as the spawning season progresses (Rich et al 2006), and that most dispersers first homed to their natal streams before dispersing to new spawning grounds (Peterson et al 2016). Studies of Atlantic salmon caught in the Teno river show that movement of individuals to other areas is rare close to spawning (Økland et al 2001) and radiotelemetry of individuals has also shown very limited movement during the breeding season (Karppinen & Erkinaro 2009). Thus, long distance movement of individuals visiting this spawning site close to spawning time is highly unlikely.…”
Section: Discussionmentioning
confidence: 99%